Possibilities of revamping of a factory of Wax for the elaboration of products of high added value - Pérez Morales, Vladimir; Villanueva Ramos, Gretel (Centro Azúcar Journal, 2012)
This work evidences a study for the reconversion of one raw wax (Process Swenson), which is not being utilized present and this product can be refined for the obtaining of new products of high added value, on the base to recover the aforementioned installation with the existent equipment at the wax refined plant of the own company and other plants of the country according to present conditions. In order to accomplish this evaluation studies done by specialists of the UCLV for obtaining biodiesel and alcohols of high molecular weight directly from laziness, which have demonstrated their feasibility for the obtaining of them with a simple and applicable technology to any sugar company of the country